Penguatan moderasi beragama melalui sikap toleransi (studi pada masyarakat desa Embonatana kecamatan Seko) - Aswar Aswar; Muhaemin; Munir Yusuf (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
This study discusses Strengthening Religious Moderation through Study Tolerance in the Embonatana Village Community, Seko District. This study aims to explain how the attitude of religious moderation and tolerance, how to strengthen religious moderation through an attitude of tolerance, what are the obstacles and solutions in strengthening religious moderation through an attitude of tolerance in the Embonatana Village community. In this study using a type of qualitative research with the stages of preparation, namely: the preparation stage, the data collection stage in the form of observation, interviews and documentation, the data processing stage which involves classifying data and compiling research results which are then described as a research report. The results of the study show that the practice of religious moderation in the Embonatana Village community has been carried out for a long time. Religious moderation practiced by the community is not entirely based on religious understanding, but is more dominated by kinship ties. Strengthening religious moderation through an attitude of tolerance is carried out through religious coaching, increasing cooperation, maintaining Sallombengang, strengthening customary law, and maintaining family ties. As for the obstacles faced are the lack of public understanding of religious teachings and tolerance, lack of public compliance with rules such as customary rules, differences in society, and increasingly tenuous family ties.